Perhitungan Manual Dan Analisis Sistem Antrian di Gerai Ice Cream Mixue Jl. Ahmad Yani Rantau Prapat - Jantina, Wiola Eka; Pitaloka, Lola Jenny; Fernando, Yogi; Saputra, Yogi; Ritonga, Irmayanti (Journal of Computer Science and Information System(JCoInS), 2025)
Queues are an unavoidable phenomenon today, manufacturing and service companies are required to be able to reduce queues in providing their services to customers. The development of the food and beverage industry is currently growing very rapidly. The food and beverage industry is still a mainstay for Indonesia's economic growth and was able to grow by 8.41% in 2018. Mixue is a food and beverage industry, the current problem is the dense queues that occur so that there is a buildup of customers and a long waiting time to be served. This data was taken for 2 days, October 20 and 26, 2024 at 12:00-22:00. The results of this study indicate that the queue system that occurs at Mixue is not optimal.